2003
DOI: 10.1128/jvi.77.5.2946-2955.2003
|View full text |Cite
|
Sign up to set email alerts
|

Exonuclease-Deficient Polymerase Mutant of Herpes Simplex Virus Type 1 Induces Altered Spectra of Mutations

Abstract: The effect of exonuclease activity of the herpes simplex virus DNA polymerase (Pol) on DNA replication fidelity was examined by using the supF mutagenesis assay. The recombinants with exonuclease-deficient Pol, containing an integrated supF gene in the thymidine kinase locus (tk), exhibited supF mutation frequencies ranging from 0.14 to 5.6%, consistent with the tk mutation frequencies reported previously (Y. T. Hwang, B.-Y. Liu, D. M. Coen, and C. B. C. Hwang, J. Virol. 71:7791-7798, 1997). The increased muta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
10
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 25 publications
0
10
0
Order By: Relevance
“…These mutant Pols exhibited defective or undetectable exonuclease activity, yet retained substantial polymerase activity. Furthermore, recombinant viruses containing the mutated Pol displayed only modestly defective replication in Vero cells and exhibited substantially increased mutation frequencies in the viral tk (23) and supF (25,27) genes accompanying altered spectra of mutations (23,29). Further characterization of these Pol mutants demonstrated that the Y7 exonuclease-deficient Pol mutant could generate heterogeneous viruses containing mutations in genes coding for DNA replicative proteins, including Pol and its accessory protein (23) UL42 (26).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These mutant Pols exhibited defective or undetectable exonuclease activity, yet retained substantial polymerase activity. Furthermore, recombinant viruses containing the mutated Pol displayed only modestly defective replication in Vero cells and exhibited substantially increased mutation frequencies in the viral tk (23) and supF (25,27) genes accompanying altered spectra of mutations (23,29). Further characterization of these Pol mutants demonstrated that the Y7 exonuclease-deficient Pol mutant could generate heterogeneous viruses containing mutations in genes coding for DNA replicative proteins, including Pol and its accessory protein (23) UL42 (26).…”
Section: Resultsmentioning
confidence: 99%
“…The mutagenesis assay and data analyses were performed as described previously (23,25). Briefly, 2 ϫ 10 4 Vero cells were infected with recombinant virus at less than 200 PFU for 72 h. Total DNA, including that prepared from virions present in the supernatants, was extracted, purified, and…”
mentioning
confidence: 99%
“…That study (13) reported that selectivity of correct over incorrect dNTP was ϳ300, whereas bacteriophage T4 and T7 DNA polymerases discriminate among dNTPs by a factor of Ͼ1000 and Ͼ100,000, respectively (14 -16). Previous studies suggested that the exo activity of HSV-1 pol contributes substantially to the fidelity of HSV replication in vivo, because mutation of the conserved exo site III of the HSV-1 pol catalytic subunit was associated with a strong mutator phenotype (10,17,18). Moreover, such pol mutants are genetically unstable and revert or recombine with high frequency (10), suggesting strong in vivo selection against an HSV-1 pol lacking exo activity.…”
mentioning
confidence: 99%
“…Accordingly, HSV-1 Pol exhibits 5=-3= polymerase and 3=-5= exonuclease activities that are characteristic functions of the replicative Pol B family (20,26,35). Polymerase activity is essential for the production of infectious progeny virus (1,13), while the 3=-5= exonuclease activity is not required for viral replication but is important for replication fidelity during viral DNA synthesis (16,17). The extreme C terminus of HSV-1 Pol is crucial for an interaction with processivity factor UL42 that is necessary for long-chain DNA synthesis and indispensable for viral replication (11).…”
mentioning
confidence: 99%